PTU-103 Intra-luminal Interleukin (il)-27 Is A Potential Future Therapeutic For Inflammatory Bowel Disease. (9th June 2014) - McLean, MH; Hanson, ML; Gold, B; Golubeva, Y; Anver, MR; Wu, X; Sun, D; Steidler, L; Durum, SK
Abstract : Introduction: Oral Lactococcus lactis engineered to express the immunoregulatory cytokine IL-27 (LL-IL27) is therapeutically active in chronic murine enterocolitis. Here, efficacy in acute colitis was examined. Methods: 2 mg 2, 4, 6-trinitrobenzene sulfonic acid (TNBS) was delivered intra-rectally in 45% ethanol or 45% ethanol alone into 6–8 week old male SJL mice. L. lactis control (LLC) or LL-IL-27 was delivered by oral gavage on 4 occasions, 24 h apart, commencing at colitis induction. Therapeutic effect was assessed clinically and histologically. Potential mechanisms of action were investigated. Results: TNBS induced an acute severe distal colitis. LL-IL-27 led to a significant reduction in disease activity index compared to LLC (4.9 vs. 8.7/12 on day 2 (p = 0.001); 3.6 vs. 7.7/12 on day 3 (p = 0.001), improved macroscopic colitis score (p < 0.05), and reduction in serum CRP (p = 0.003, day 2). Histological colitis score was reduced (p = 0.035) with significant improvement in mucosal ulceration (p = 0.008). TNBS increased expression of distal colon Il6, Il1β, Tnf, and Il10, assessed by RT-PCR, with no differential effect seen with LL-IL-27. However, LL-IL-27 led to a significant reduction in IL-6 (p = 0.002), IL-1β (p = 0.001) and TNF (p = 0.014) protein assessed by ELISA. A significant reduction in colonic mucosal myeloperoxidase + neutrophil infiltrate was seen in the LL-IL-27 group (p = 0.004), along with a significant decrease in the neutrophil chemoattractant CXCL2 (p < 0.001). LPS induced CXCL2 gene and protein expression in macrophages was not inhibited by recombinant IL-27 in vitro, suggesting an indirect mechanism in vivo . Peri-ulceration distal colonic mucosa was isolated by laser capture microdissection and RNA applied to mouse Genome 430 2.0 Affymetrix microarray. Principal component analysis grouped mice by treatment. 285 genes were differentially expressed (>/<1.5 fold change in expression plus p < 0.05) in the LL-IL27 group, including a striking down-regulation of mucosal humoral response genes, (for example, probe sets for IgA heavy chain (-20.6 fold), Igκ chain var1 (-19.0 fold), Igλ chain CR2 (-4.8 fold)). This was not explained by a reduction in CD45R/B220 + B cell infiltrate (p = 0.02). Up-regulated genes include those involved with anti-microbial defense ( RegIIIb, Clec7A, ligp1 ) and innate immune response ( cxcl10, cxcl9 ). Conclusion: Intra-luminal IL-27 represents a potential therapy for human inflammatory bowel disease and acute colitis of differing aetiologies. Disclosure of Interest: M. McLean: None Declared, M. Hanson: None Declared, B. Gold: None Declared, Y. Golubeva: None Declared, M. Anver: None Declared, X. Wu: None Declared, D. Sun: None Declared, L. Steidler Employee of: ActoGenix, S. Durum: None Declared.